Perancangan Value Stream Mapping dan Upaya Penurunan Lead time pada Bagian Procurement-Purchasing di PT X - Yansen, Oey; Bendatu, Liem Yenny (Jurnal Titra, 2013)
PT X is one of the biggest manufacturer companies in Indonesia. Achieving one of its missionâcontinuous improvement, PT X keeps on making the new innovations and solution breakthroughs for its business process. At this opportunity, the improvement will focus on the procurement and purchasing departments, responsible for the companyâs daily transactions.The first stage in Value Stream Mapping is Current State Mapping, providing the activities of the current condition and their lead time. Next step is analysis, where all the wastes are identified and solutions are developed. Lastly, Future State Mapping is the continuation of the previous stageâgenerating the new process involving the new lead time.As the Value Stream Mapping is developed, it is found 3 waste categories, i.e. over processing, waiting, and unnecessary movement. Solutions are given to reduce those wastes and will reflect in the future state mapping. It is believed that the future mapping will shorten processâ lead time of the pre-purchase requisition by 33.25% and after purchase requisition by 28.17% for FSS and 23.53% for M&S category.